(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The study examined the sustainability strategies for building maintenance practices. This study adopted a surveys research style. The research population comprises of students, staff of works department and physical planning units in Nnamdi Azikiwe Univeristy Awka. cluster sampling technique was adopted for the study. The instrument used was a structured questionnaire. To ensure the validity of data collection instrument, the questionnaires was submitted to the researchers supervisor who assessed the content and structure. The test for reliability of the instrument was done using the Cronbach’s Alpha. To ensure the validity of data collection instrument, the questionnaires was submitted to the researcher’s supervisor who assessed the content and structure. The study showed that routine maintenance work like painting, servicing equipment’s and machineries, e.t.c is the mostly adopted sustainability strategy for the maintenance of buildings and facilities in Nnamdi Azikiwe University. It was concluded that adopting environmentally conscious approaches significantly enhances the longevity, efficiency, and cost-effectiveness of buildings. One of the recommendations made was that the institution should adopt proactive sustainability strategies such as routine maintenance work, process management and integrated project delivery system, as they are more economical and effective.